Role of local instillation of one percent feracrylum and haemocogulase on wound healing - Singh, Krishna Kumar; Dhruv, Kamlesh; Patle, D. R.; Paikra, U. S. (International Journal of Research in Medical Sciences, 2016)
Background: The introduction of increasingly complex and major surgical procedures during the last 50 years has inevitably been accompanied by greater problems in wound healing. Fortunately, modern surgery is relatively safe, certainly by comparison with situation 50 years ago, but it cannot be said that it is totally devoid of risks or complications, and problems of wound healing are encountered in every surgical specialty. Indeed, in various ways these complication account for a large part of morbidity and mortality of surgical treatment. The present study has been carried out to evaluate role of local instillation of 1% feracrylum and haemocoagulase on wound healing. Methods: The present study was carried out in 100 patients in the Department of General Surgery, S.S. Medical College and associated G.M. Hospital and Sanjay Gandhi Memorial Hospital, Rewa (M.P.), India. The material for the study comprised of randomly selected 100 patients. A thorough clinical examination was done to assess general condition of patients and systemic disorder. Local examination was done to make a surgical diagnosis and associated problem. In case of surgical emergency, on arrival of patient clinical examination was immediately started and history asked during resuscitation of the patient. All relevant procedures were performed before surgery. Appropriate surgical procedures were performed. Suitable local haemostatic was applied. The wound inspected on 3rd, 7th and 14th day of presence of swelling, tenderness, colour change, discharge, scar tissue and changes were recorded. Results: Most of the patients were between 21-30 years and 50 and above. The youngest being 3 years and the eldest being 75 years old. Majority of patients were operated for Perforation Peritonitis (28%) and Hernia (26%). Next common group was Intestinal Obstruction (9%) and Cholecystectomy (7%). Out of 100 cases operated 60 were as planned and rests were as emergency cases. 1% Feracrylum and Haemocoagulase was used in equal number of cases. In 24 cases 1% Feracrylum was instilled subcutaneously in 10 cases instilled at intermuscular level and in 16 cases instilled at both level. In 23 cases Haemocogulase was instilled subcutaneously in 14 cases instilled at intermuscular level and in 13 cases instilled at both level. All cases Skin Wound was closed in Interrupted fashion. Conclusions: Good surgical technique plays key role in post-operative wound healing. The essential of good surgical technique include gentle handling of tissues, meticulous haemostasis, and prevention of dead space in the wound and avoidance of tissue necrosis resulting from excessive use of diathermy or strangulation of tissues by Ligatures. 1% Feracrylum and Haemocoagulase are helpful in decreasing local infection rate by decreasing post-operative capillary oozing.